Case Report: Atypical Manifestations Associated With FOXP3 Mutations. The “Fil Rouge” of Treg Between IPEX Features and Other Clinical Entities? - Gentile, Micaela; Miano, Maurizio; Terranova, Paola; Giardino, Stefano; Faraci, Maura; Pierri, Filomena; Drago, Enrico; Verzola, Daniela; Ghiggeri, Gianmarco; Verrina, Enrico; Angeletti, Andrea; Cafferata, Barbara; et al. (Frontiers in Immunology, 2022)
Introduction. The Forkhead box protein P3 (FOXP3) is a transcription factor central to the function of regulatory T cells (Treg). Mutations in the FOXP3 gene lead to a systemic disease called immune dysregulation, polyendocrinopathy and enteropathy, X-linked syndrome (IPEX) characterized by the triad of early-onset intractable diarrhea, type 1 diabetes and eczema. Atypical presentation of IPEX has been reported. Method. We report rare cases with equivocal clinical associations that included inflammatory, kidney and hematologic involvements screened with massively parallel sequencing techniques Results. Two patients with hemizygous mutations of FOXP3 [c.779T>A (p.L260Q)] and [c.1087A>G (p.I363V)] presented clinical manifestations not included in typical cases of IPEX: one was a 16-year male with an initial clinical diagnosis of ALPS who developed proteinuria and decreased kidney function due to membranous nephropathy, an autoimmune renal condition characterized by glomerular sub-epithelial antibodies. The second patient was a 2-year child with bone marrow failure who developed the same glomerular lesions of membranous nephropathy and received a bone marrow transplantation. High levels of IgG4 in serum, bone marrow and kidney led to the definition of IgG4 related kidney disease (IgG4 RKD) in this young boy. Circulating Treg levels were normal in the former case and very low in the second. Conclusion. Two atypical associations of functional mutations of FOXP3 are described that include ALPS and IgG4 RKD. Membranous nephropathy leading to renal failure completed in both cases the clinical phenotypes that should be included in the clinical panorama of FOXP3 failure.